The Role Of Human Capital And Total Factor Productivity In Promoting Economic Growth: A Comparative International Study - Ahmed Almosabbeh, Imadeddin (University of Eloued جامعة الوادي, 2019)
The aim of this study is to test the existence of a positive relationship between the human capital and economic growth in a group of countries. The study has employed ARDL method on data for the period 1950-2014. The results show that there is a long-term relationship between human capital and economic growth in South Korea, South Africa, the United States, France and Germany, while there was no significant correlation in Japan, Saudi Arabia and Egypt. As for the effect of the total factor productivity, it was found that their effect is significant in all countries except Egypt. The study suggests the continued accumulation of human capital and that the output of education be directly involved in the production process.
مجلة رؤى المجلد التاسع العدد الأول
Keywords: Human Capital, Economic Growth, Total Factor Productivity, Knowledge Economy. (JEL) Classification : O47, J24